Financial Development in Asia : The Way Forward - Eichengreen, Barry J. (Book collections on Project MUSE., 2004)
Professor Eichengreen has published widely on the international monetary and financial system. His books include Capital Flows and Crises, and Financial Crises and What to Do About Them. Data shows that Emerging Asia relies less on bonds and more on banks than developed countries. What costs, if any, do Asian countries incur as a result of their heavy dependence on bank finance and the underdevelopment of their bond market? Barry Eichengreen addresses the questions: what benefit ...